The decision of whether to have a child: Does couple disagreement matter? - Maria Rita Testa; Laura Cavalli; Alessandro Rosina (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2012)
Most of the international studies on fertility are based on a female perspective. A major difficulty in couple-level research is the need for high-quality data that includes information on both partners. Using couple data from a longitudinal study conducted in Italy [2003-2007], a country with persistently low fertility levels, we examined the effect of disagreement within a couple about childbearing behaviour. The starting point was the hypothesis advanced in an earlier study that Italian women prevail in reproductive decision-making, because childbearing lies mainly in their sphere of influence. The data revealed that the decision rules are parityspecific. At parities zero and one, the disagreement produced an intermediate childbearing outcome irrespective of which partner wanted a(nother) child; while at higher parities, an asymmetrical veto power model in which the female partner had greater influence was observed. The findings suggest that the predictive power of short-term fertility intentions strongly improves if both partners' views are considered in fertility models, and thus support the adoption of couple analysis in fertility research.
Keywords: 300; Fertility decision-making; reproductive behaviour; couple disagreement; childbearing intentions; child-timing intentions; partner context; Frauen; Fertilität; Familienplanung; Ehe; Italien